Detection of Khapra Beetle environmental DNA using portable technologies in Australian biosecurity - Trujillo-González, Alejandro; Trujillo-González, Alejandro; Thuo, David; Divi, Uday; Sparks, Kate; Wallenius, Thomas; Gleeson, Dianne (Dryad, 2021)
Khapra beetle, Trogoderma granarium Everts, 1898, is a serious pest of
stored grain products globally. Environmental DNA (eDNA)-based methods
offer sensitive detection tools used to inform biosecurity officers on the
presence of high-risk pests. This study tested laboratory and portable
molecular technologies to detect khapra beetle environmental DNA extracted
from dust samples collected during biosecurity responses (Tuggeranong and
Fyshwick) to khapra beetle incursions in Australia. Airborne and floor
dust samples were collected opportunistically using handheld vacuum
cleaners and eDNA was extracted using either field or laboratory-based
extraction methods and analyzed using laboratory benchtop real time PCR
machines and portable machines with two TaqMan and one LAMP-based assay.
We successfully collected, extracted, and amplified khapra beetle eDNA
from dust samples by qPCR, but failed to amplify T. granarium eDNA using
LAMP. The Laboratory qPCR machine showed significantly higher mean Ct
values (p < 0.001) and significantly higher positive detections
for both assays (p < 0.001) compared to the portable
thermocycler. DNA yield was significantly higher in samples extracted
using laboratory-based kits compared to field kits (p < 0.001)
for both vacuumed and airborne samples (Mean DNA ± S.D. = 5.52 ± 4.45 and
4.77 ± 1.68 ng/μL, respectively), compared to field kits, (1.75 ± 1.17 and
1.36± 1.29 ng/μL for vacuumed and airborne samples, respectively). There
were no significant differences in DNA yield between collection methods or
differences in amplification associated to extraction or collection
methods in either platform tested in this study. Portable technologies
tested in this study (Franklin™ Real Time Thermocycler and Genie III)
accurately amplified all tissue derived DNA during assay optimisation and
field testing, highlighting the capacity of these technologies to
complement biosecurity in confirming specimen ID. There was a high
incidence of positive detections in field negative controls (Tuggeranong =
12.3 % and Fyshwick = 50 %), mostly attributed to the use of contaminated
vacuum cleaners. We discuss suitable methods to minimize sample
cross-contamination, the potential of portable molecular technologies as
tools for biosecurity applications, and the suitability of eDNA-based
molecular detection methods to complement global trade biosecurity for one
of the most invasive and important grain pests worldwide.
This dataset contains amplification data for all environmental DNA samples
collected during Australian biosecurity responses for Khapra beetle. All
Samples were run in triplicate (including negative extraction blanks,
field and negative controls) using TaqMan assays designed in previous
studies. We considered samples as positive if amplification crossed a
common threshold determined individually within each qPCR run and if
detections occured within each assay's cutoff values. If no positive
amplification was observed in any qPCR replicates then samples were deemed
negative. Quantitative PCR reactions were done using the ViiA™ 7 Real-Time
PCR System (Applied Biosystems, Vic., Australia) and in a Franklin™
portable Realtime Thermocycler (Biomeme, USA). All data associated to
exporting/importing companies have been removed to ensure confidentiality.
Keywords: FOS: Environmental biotechnology